Profit Analysis of Beef Cattle Business on Sinar Pagi Livestock Group, in Limapuluh Kota District, West Sumatra - Edwin, Tevina; Arfa'i; Rastosari, Adisti; Utami, Yolani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
This study aims to determine the income and analyze the profit level of the beef cattle business owned by the Sinar Pagi livestock group in Limapuluh Kota Regency, Sumatera Barat Province. This research contributes to the wider debate on improving rural livelihoods and achieving sustainable agricultural development, and is essential for understanding the profitability of smallholder livestock enterprises. The results of this research will provide insights into the financial sustainability of their operations and will inform strategies for the optimisation of their business performance. The research was carried out using a case study method with 16 key informants, also members of the Sinar Pagi livestock group. Data were analyzed with descriptive quantitative methods. The study results show that the income earned by this livestock group in one year of research is IDR 6,471,775, with a profit rate of 1.08/year. It can be concluded that the Sinar Pagi livestock group only gets a profit of 8%, and this profit has not been able to meet the needs of the farmer's life.